Fear of the unknown: One fear to rule them all? - Carleton, R. Nicholas (Journal of anxiety disorders, 2016)
•Contextualizes the search for fundamental fears.•Reviews and revises the criteria for fundamental fears.•Synthesizes current research on potential fundamental fears.•Posits fear of the unknown as a, possibly the, fundamental fear. The current review and synthesis was designed to provocatively develop and evaluate the proposition that “fear of the unknown may be a, or possibly the, fundamental fear” (Carleton, 2016) underlying anxiety and therein neuroticism. Identifying fundamental transdiagnostic elements is a priority for clinical theory and practice. Historical criteria for identifying fundamental components of anxiety are described and revised criteria are offered. The revised criteria are based on logical rhetorical arguments using a constituent reductionist postpositivist approach supported by the available empirical data. The revised criteria are then used to assess several fears posited as fundamental, including fear of the unknown. The review and synthesis concludes with brief recommendations for future theoretical discourse as well as clinical and non-clinical research.